Kardiochirurgia dorosłychElective surgery for aneurysm of the ascending aorta and arch – early results - Widenka, Kazimierz; Stącel, Tomasz; Kolowca, Maciej; Szymanik, Izabela; Mazur, Witold; Bąk, Janusz; Kurowicki, Arkadiusz; Stożyński, Nikodem; Żurek, Sławomir; Oliwa, Maciej (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2008)
Background: Aneurysm of the ascending aorta is often a concomitant disease. It is commonly believed that replacement of the aorta is a high-risk procedure. Therefore it is often avoided during complex procedures. Aim: To assess the early results of the elective operation for aneurysm of the ascending aorta and aortic arch as a concomitant procedure. Material and Methods: This retrospective study included 52 patients (40 men, 12 women), mean age 62.5±10.45 years, undergoing elective ascending and aortic arch aneurysm operations (50 ascending aorta aneurysms, 1 ascending and arch aneurysm, 1 arch aneurysm). Mean Euro score log. was 12.8±8.17% and EF 53.3±9.62%. Mean diameter of the ascending aorta was 53.1±8.66 mm. Mean cross-clamp time and CPB time were 87.0±30.03 and 120.6±32.20 min. respectively. Results: There was no hospital mortality. 48 patients (86.28%) received anti-fibrinolytic therapy; mean chest tube drainage was 847.6±410.73 ml. 1 patient required re-exploration for bleeding. Mean need of blood and plasma transfusion was 2.9±1.40 and 2.4±0.77 units respectively. Mean ICU and hospital length of stay were 2.8 (±2.40) and 7.9 (±3.12) days respectively. The following complications were observed in the ICU: atrial fibrillation – 14 patients (26.92%); low output syndrome – 2 (3.85%), one of whom required IABP; pneumonia – 2 (3.85%); VF – 1 (1.92%). We did not observe neurological events except for 2 postoperative confusions (3.85%). There was 1 episode of acute transient renal failure requiring haemofiltration (1.92%). The following complications were recorded in the ward: atrial fibrillation – 11 patients (20%); hydrothorax – 5 patients (9.61%); infection of urinary system – 3 patients (5.77%). Other less common complications were: cholecystitis (n=1), laryngitis (n=1), confusion (n=1), tachybrady syndrome (n=1), sternal wound infection (n=1), and transient increase of creatinine level up to 1.7 mg/dl (n=1). Conclusions: In view of the low mortality and morbidity, ascending aortic replacement in addition to other cardiac procedures should be recommended if the ascending aortic diameter exceeds 45 mm.